Islamic Guidance: Synergy and Collaboration of Islamic Teacher and Guidance and Counseling Teacher in Shaping Students' Religious Character at SDN 09 Kota Bengkulu - Novriyana, Yola; Alimni, Alimni (IKIP Siliwangi, 2024)
In reality, what happens in the world of education is moral decline. The existing education seems more oriented towards the transfer of knowledge and neglects the cultivation of moral and ethical values. The purpose of this study was to determine the synergy and collaboration of Islamic teachers and guidance and counseling teachers in shaping students' religious character at SDN 09 Bengkulu City. This research is field research, this research method is not directed to explain the relationship nor does it predict or implicate what will happen when a variable is manipulated. This research was conducted at SDN 09 Bengkulu City in 2023. Data collection used observation, interviews and documentation. Data analysis used interactive analysis model of Miles & Huberman. The conclusion of the research shows the strategy and collaborative islamic teacher and guidance and counseling teacher in instilling religious character to students by acting as educators, learning resources, facilitators, models, advisors and motivators. The implications of this research can be used as consideration and reference material for Islamic teachers and guidance and counseling teachers, and further researchers both theoretically and practically